روش بازیابی اندیشه های کلامی شیخ کلینی - esmail esbati (پژوهش‌نامه کلام تطبیقی شیعه, 2023)
Muhammad ibn Ya'qub al-Kulayni Rāzī (d. 329 AH), in the compilation of the most important Shia hadith collection, before dealing with jurisprudential issues, presented the religious traditions in two volumes. This section is one of the most important sources of Shia religious hadiths. The best use of this section is to find out the thoughts and the way Shaykh Kulayni looks at every issue. Since Al-Kafi is the only piece left of Shaykh Kulayni, which was written in the style of muhaddiths and not theologians, extracting the theological perspective of Shaykh Kulayni when he faces challenges, such as whether his opinions can be understood based on his book, which is a work of hadith. What should be done to extract his opinions? This research, in a descriptive-analytical way, seeks to find evidence and clues to extract the theological thoughts of Shaykh Kulayni. Shaykh Kulayni's theological opinions can be extracted by careful naming of chapters, the type of arrangement of chapters and books, attention to the general content of the narrations of a chapter, accuracy in the content of narrated narrations and their comparison with a group of narrations that have been left out. In addition, Sheikh Kalini has some comments in the introduction of Kafi and sometimes among the narrations, which, although few, are interesting.